The effects of different multidirectional plyometric sequences on shooting, balance, and neuromuscular performance in professional male basketball players - Brini, S.; Yagin, F. H.; Calleja-González, J.; Sansone, P.; Badicu, G.; Bouassida, A.; Castagna, C.; Greco, G.; Alghannam, A. F.; Ardigo, L. P.; Delextrat, A. (PLOS ONE, 2025)
Objective Repeated multidirectional jumps are highly specific movements in basketball, which may be important to integrate the training routine. Accordingly, this study aimed to assess the effects of three different multidirectional plyometric jumping sequences on shooting, balance, and neuromuscular performance in professional, male basketball players.